Perlindungan Hukum Terhadap Lelang Objek Jaminan Berdasarkan Perspektif Hukum - Dhiwatsani Yudhistira; Gunawan Djajaputra (LPPM Universitas Ekasakti Padang, 2024)
This research aims to carry out collateral auction responsibilities, especially for customers, towards auction officials in the auction of collateral objects with a focus on a legal perspective. The auction execution process often involves complex problems, raising questions regarding the rights of the pawned object and legal protection for both the customer and the auction official. This research will analyse the legal framework that regulates customer rights and also the rights of auction officials regarding auctions of collateral objects without notification. This legal approach will include a review of applicable auction regulations, property rights, and legal protection for customers and auction officials. In addition, this research will evaluate the extent of applicable legal protection.